Specific parameters of the thromboelastographic profile of patients with COVID-19 in the intensive care unit - A. V. Samorodov; K. n Zolotukhin; D. V. Zabolotskiy; Yu. S. Аleksandrovich; L. I. Bashirova (Вестник анестезиологии и реаниматологии, 2020)
The objective: to study the hemostatic system of patients diagnosed with the novel new coronavirus infection and compare the data obtained with hemostatic system parameters in patients with advanced deep vein thrombosis/pulmonary embolism without COVID-19.Subjects and methods. A single-center prospective study with retrospective control was conducted in Anesthesiological and Intensive Care Department No. 1 of Kuvatov State Medical University (Ufa) in April - May 2020, the objective of the study was to investigate the hemostatic system of patients with confirmed new coronavirus infection, patients diagnosed with venous thrombosis in 2012-2014, and a group of healthy volunteers.Results. Evaluation of the hemostasis system in patients with thrombosis and patients with COVID-19 demonstrates the same type of changes: MA, Angle, G indices increase according to thromboelastography results, as well as D-dimer and fibrinogen levels increase, while antithrombin III activity decreases.Conclusion. Thus, TAG may be crucial for accurate identification of patients with advanced increased risk of thrombosis and thus possibly avoid unnecessary anticoagulation in patients at low risk of thrombosis.